Kingdom of the Netherlands - Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper examines the long-term issues with pension expenditures in the Netherlands. The paper highlights that the public pension for a single person is equal to 70 percent of the (statutory) minimum wage. The minimum wage and public pensions thus move in lock-step; they are both by law indexed to contract wages in the private sector. This paper examines the structural policies of the Netherlands. Real wages and employment growth are also analyzed.